1983
DOI: 10.1007/bf02534640
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of fatty acid, glycerol and a monoglyceride analogue by rat cardiac myocytes and perfused hearts

Abstract: Studies have been conducted on the uptake and metabolism of unesterified fatty acid, free glycerol and 1-hexadecyl glyceryl ether by rat cardiac myocytes, and of fatty acid, intact triglyceride and the glyceryl ether by perfused rat hearts. Cardiac myocytes efficiently extracted, oxidized and esterified oleic acid, but demonstrated little ability to utilize free glycerol. Although the glyceryl ether was efficiently extracted by myocytes, it was neither hydrolyzed or esterified. The perfused heart also extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In cardiac myocytes, glycerolipid synthesis requires free fatty acids (FFAs) and glycerol-3-phosphate (G3P). While FFAs can be derived from transporter-mediated uptake across the plasma membrane [ 62 ], myocytes have a relatively low capacity for free glycerol uptake; therefore, there is little contribution of glycerol kinase to G3P synthesis [ 63 , 64 ]. However, G3P can be generated from dihydroxyacetone phosphate (DHAP) by glycerol-3-phosphate dehydrogenase ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…In cardiac myocytes, glycerolipid synthesis requires free fatty acids (FFAs) and glycerol-3-phosphate (G3P). While FFAs can be derived from transporter-mediated uptake across the plasma membrane [ 62 ], myocytes have a relatively low capacity for free glycerol uptake; therefore, there is little contribution of glycerol kinase to G3P synthesis [ 63 , 64 ]. However, G3P can be generated from dihydroxyacetone phosphate (DHAP) by glycerol-3-phosphate dehydrogenase ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol is not reutilized to any significant extent by the myocardium. This is because of the absence [51] or very low activity [52] of glycerokinase and is supported by studies demonstrating minimal incorporation of ["%C]glycerol into glycerolipids in perfused heart [53] or cardiac myocytes [54]. Although de Groot et al [55] have criticized the validity of glycerol release as a measure of cardiac lipolysis on the grounds that sonicated heart homogenates can catalyse the dephosphorylation of glycerol 3-phosphate, the experimental conditions used by de Groot et al [55] would have disrupted lysosomes and are not relevant to whole-cell conditions.…”
Section: Tag Turnovermentioning
confidence: 84%
“…The latter also involves MGAT. Tamboli et al [54] have shown that the 1hexadecyl glycerol ether analogue of MAG is not esterified by myocytes or perfused heart, a finding that might suggest the absence of MGAT activity. However, although good substrates for the intestinal form of MGAT [61], 1-or 2-alkylglycerols are very poor substrates for the form of MGAT that is expressed in liver from suckling rats [61][62][63] and which is very specific for 2acylglycerol substrates [61].…”
Section: Tag Turnovermentioning
confidence: 99%
“…While FFAs can be derived from transporter-mediated uptake across the plasma membrane, 282 myocytes have a relatively low capacity for free glycerol uptake; therefore, there is little contribution of glycerol kinase to G3P synthesis. 283,284 However, G3P can be generated from DHAP by glycerol-3-phosphate dehydrogenase (Fig. 26A).…”
Section: Pfk Regulates Glycerolipid Synthesis In Cardiomyocytesmentioning
confidence: 99%